2012
DOI: 10.1111/j.1464-410x.2012.11434.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of initially expectantly managed patients with low or intermediate risk screen‐detected localized prostate cancer

Abstract: Study Type – Therapy (outcomes) Level of Evidence 2b What's known on the subject? and What does the study add? Active surveillance aims to reduce overtreatment by selecting patients with low risk prostate cancer (PCa) based on favourable disease characteristics. However, most studies on active surveillance do not have long‐term results available; in particular, data on patients with intermediate risk disease are lacking. Our findings demonstrate that withholding radical treatment in men with low or intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 24 publications
7
95
0
2
Order By: Relevance
“…In that cohort, most patients had a PSA <10 ng/mL (median 5.3 ng/mL). 9 Taken together with our results, this suggests that patients with an elevated PSA over 10 ng/mL as the only criterion for intermediate-risk classification may have equivalent outcomes to low-risk patients.…”
Section: Discussionsupporting
confidence: 53%
“…In that cohort, most patients had a PSA <10 ng/mL (median 5.3 ng/mL). 9 Taken together with our results, this suggests that patients with an elevated PSA over 10 ng/mL as the only criterion for intermediate-risk classification may have equivalent outcomes to low-risk patients.…”
Section: Discussionsupporting
confidence: 53%
“…The limitation of this observation is the relatively short mean follow-up of 28.3 months. For PCa diagnosed by core needle biopsy, Bul et al [26] also reported no difference in tumour-specific survival between the patients with low-and intermediate-risk disease in the case of a longer mean followup. At a mean follow-up of 7.4 years, the tumour-specific survival was 99%, with no differences between the risk groups; however, more patients in the intermediate-risk group received invasive therapy (53.9 vs 39.9%; P = 0.006).…”
Section: Discussionmentioning
confidence: 99%
“…PIVOT results did not show a significant difference in the number of prostatecancer specific deaths between radical prostatectomy patients and patients under observation [16]. Multiple studies have reported 94-99% 10-year cancer-specific survival rates in men under active surveillance for low-risk and intermediate-risk prostate cancer, compared to the 90% rate reported for a similar cohort treated by radical prostatectomy [42][43][44][45]. There is no difference in overall survival rates between patients who remain on surveillance and those who seek deferred treatment [46].…”
Section: Active Surveillancementioning
confidence: 66%